Empowering Bureaucracies in Municipal International Policies: Organizational Structures and Governance Transformation of Japanese Municipal Overseas Offices in Southeast Asia - Fujiwara, Naoki (Policy & Governance Review, 2025)
In today's globalized society, achieving balanced national development requires regional strategies that emphasize both domestic and international collaboration. Municipalities must attract foreign tourists, promote local product exports, and support SMEs' overseas expansion. These policies shifted from traditional administrative approaches to those demanding short-term results and practical benefits. This necessitates innovative policy formulation by entrepreneurial municipalities. This study explores the organizational and governance structures that strengthen local bureaucratic systems to effectively implement these international policies. The research methodology includes analyzing policy documents related to Japanese municipal international policies and conducting field interviews with 36 expatriates, primarily from Japanese municipal overseas offices in Singapore and Bangkok, between 2020 and 2023. The findings reveal that in the VUCA era, international municipal networks evolved from one-on-one sister-city relationships to multi-city networks focused on information sharing and project development. Additionally, the organizational structures of international policy-executing bodies increasingly involve partnerships with national agencies and collaborations between municipalities and private companies, including outsourcing certain tasks. Based on these insights, this study presents a developmental model that categorizes international municipal policies into three stages: Traditional Administration, New Public Management, and Network Governance. It also offers policy recommendations for leadership, policy evaluation, and human resource development to empower local bureaucracies.